Management of the enterprise innovative activities - Sun, Mingxiao (Харківський національний автомобільно-дорожній університет, 2024)
In the qualification paper, the concept of "innovation activity" has been refined. The paper examines various approaches to the classification of innovations. Additionally, different methodologies and approaches to evaluating innovation activity were analyzed. Based on this analysis, an algorithm in the form of stages for managing innovation activity in enterprises has been developed. This algorithm forms and implements consecutive stages of planning innovation activity, enabling domestic enterprises to optimally respond to the challenges posed by internal and external environmental factors. Methodological foundations for assessing and selecting directions of innovation activity have been proposed, which, unlike existing methods, are based on the application of functional-target analysis. Recommendations for forming a portfolio of innovation projects for RTE have been developed using morphological analysis. Forecast assumptions regarding the development of the research object – the formation and selection of a prioritized portfolio of innovation projects under changing external environmental conditions.
Keywords: innovations; innovation activity; portfolio; innovation project; business processes; hierarchy analysis; innovation management